Distinct biomarker and behavioral profiles of human papillomavirus-related oropharynx cancer patients by age. (February 2020) - Fakhry, Carole; Waterboer, Tim; Westra, William H.; Rooper, Lisa M.; Windon, Melina; Troy, Tanya; Koch, Wayne; Gourin, Christine G.; Bender, Noemi; Yavvari, Siddhartha; Kiess, Ana P.; Miles, Brett A.; et al.
Highlights: Sexual behavior is a risk factor for HPV-OPC diagnosed at younger, middle and older age. Intensity of sexual exposure may explain age of disease onset. HPV high-risk type in tumor differs by age. Abstract: Background: HPV-positive oropharynx squamous cell cancer (HPV-OPC) patients were initially described as younger, however incidence has increased among older age-groups. It is unknown why some patients present at a younger age and others at a later age. Methods: Multi-institutional prospective study of HPV-OPC cases (n = 163) and matched controls (n = 345) with detailed behavioral survey, and serum tested for HPV antibodies by fluorescent bead-based technology. Age at diagnosis was used to stratify patients into younger (≤50 years), middle-age (51–65), and older (>65). Results: By age, demographic characteristics were largely similar, but HPV biomarkers and sexual acts differed. Younger cases were more likely to be HPV16-positive than older cases (100% vs 77%, p = 0.009). Similarly, younger cases were more likely to be HPV16 E6 or E7 seropositive (100% vs 82%, p = 0.03). Younger cases had a higher number of oral sex partners per year, a marker of sexual intensity (sex-years, p = 0.003), but a similar number of lifetime oral sex partners (measure of cumulative sexual exposure), compared to older cases. While sex-years were higher for younger cases and controls, cases had significantly higher sex-years than matched controls in each age-group (p < 0.001). Younger patients were also more likely to perform oral sex at sexual debut, and were younger at sexual debut (each p < 0.03). Conclusions: Younger, middle-age and older HPV-OPC have distinct biomarker and behavioral profiles. Younger HPV-OPC cases have higher intensity of sexual exposure than older cases and controls, which may in part explain earlier disease onset. The distribution of HPV16-positive tumors among HPV-OPC differs by age group.